Comparative risk impact of edoxaban in the management of stroke and venous thromboembolism - Tellor KB; Van Tuyl JS; Armbruster AL (Dove Medical Press, 2016)
Katie B Tellor, Joseph S Van Tuyl, Anastasia L Armbruster Department of Pharmacy Practice, St Louis College of Pharmacy, St Louis, MO, USA Abstract: Edoxaban, a factor Xa inhibitor, was approved by the United States Food and Drug Administration in 2015 for stroke prevention in nonvalvular atrial fibrillation and treatment of venous thromboembolism. It is the fourth target-specific oral anticoagulant to be approved. Edoxaban is noninferior for efficacy compared to warfarin for both approved indications. Edoxaban is superior to warfarin for the first major or clinically relevant nonmajor bleeding event in venous thromboembolism and major bleeding in nonvalvular atrial fibrillation. Edoxaban is dosed once daily for both indications and requires dose adjustment for renal function. In patients with nonvalvular atrial fibrillation, use is not recommended in patients with a creatinine clearance greater than 95 mL/min due to reduced efficacy. Edoxaban offers a new therapeutic alternative to the currently available options in the market. Keywords: anticoagulation, stroke, deep vein thrombosis, pulmonary embolism, atrial fibrillation, Savaysa™